2021
DOI: 10.17770/sie2021vol1.6154
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Motivation to Attend Physical Education Classes in Universities of Ukraine

Abstract: The article is dedicated to the research of priority motives according to attending “Physical education” classes by I and II year students from universities of Ukraine. The goal of the research is to determine the ratings of students’ motivation towards attending physical education classes in the universities in Ukraine. The methods of research are analysis and generalization of scientific methodologic literature data, sociologic methods (questionnaire) and mathematical statistics methods. The questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The findings revealed that receiving course credits (57%) and body strengthening (47.9%) were significant motivators. Male students prioritized improving physical efficiency (26.5%), while female students prioritized the desire to become fit (35.2%) [28]. Our study revealed walking and cycling as popular activities across all locations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The findings revealed that receiving course credits (57%) and body strengthening (47.9%) were significant motivators. Male students prioritized improving physical efficiency (26.5%), while female students prioritized the desire to become fit (35.2%) [28]. Our study revealed walking and cycling as popular activities across all locations.…”
Section: Discussionmentioning
confidence: 75%
“…In a 2021 study, motives for attending Physical Education classes among Ukrainian university students were examined [28]. The findings revealed that receiving course credits (57%) and body strengthening (47.9%) were significant motivators.…”
Section: Discussionmentioning
confidence: 99%
“…Modern physical education is going through intensive transformations aimed at increasing the effectiveness of learning and increasing the motor activity of children. The researchers (Bodnar et al, 2015;Khanikiants et al, 2021;Kukhar, Sorokolit, Yavorskyy & Khanikiants, 2021) indicate the importance of modernizing approaches to physical education. One of the key trends is the use of the modern means of physical education in the educational process.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of Ukrainian scientists have devoted their articles to the issue of selection of means for remote physical education lessons. Scientists emphasize the difficulties of physical education during the period of quarantine and distance learning (Kryviencova, Klimenchenko, & Іvanov, 2020;Bashtenko & Stanieva, 2021;Іlnitska, Semashko, & Kryviencova, 2021;Sapiegіna, 2022); peculiarities of physical education of schoolchildren and the necessity to select innovative forms for distance learning period (Poproshaiev, Muntjan, & Goienko, 2020;Cherepovska, 2021;Cybulko & Globa, 2021;Mozoliev, 2022), as well as the study of pupils' motivation to engage in physical exercises (Kukhar, Sorokolit, Yavorskyy, Rymar. & Khanikiants, 2021); the effect of distance learning on pupils' motor activity (Sirovatko & Yefremenko, 2022); issues regarding adaptation of pupils and parents to remote physical education lessons (Maslova et al, 2021), their interaction in the conditions of distance and mixed learning: two-years' experience of overcoming the negative impact of the COVID-19 pandemic (Malykhin, Aristova, & Kalinina, 2022); peculiarities of physical education of schoolchildren in the conditions of martial law (Lytvyn, 2022;Zabіjako, 2023); the effect of distance learning on motor activity of schoolchildren in the conditions of martial law (Vashсhuk, 2022); application of an integrated approach in modern school in the context of distance learning (Horbatiuk, Polishchuk, Kuchynska, & Blashkova, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%